Juridical Analysis of Online Prostitution Service Users in the Indonesian Legal Framework - Novritsar Hasitongan Pakpahan; Rio Saputra; Didit Darmawan; Boby Eka Chandra Nugraha; Yusuf Fahrizal Mujisulistyo (Jurnal Hukum Lex Generalis, 2024)
The phenomenon of online prostitution in Indonesia presents complex legal challenges, triggered by the rapid development of information technology and the shift in prostitution operations from conventional to online. This study examines Indonesia's criminal legal framework in relation to online prostitution, highlighting the absence of specific legal norms to regulate online prostitution service users. This causes service users to often escape the law, even though their activities clearly violate social and moral norms. A normative juridical approach was used in this research, involving the analysis of relevant legislation and legal doctrine. The results show that existing regulations have not effectively addressed online prostitution, often excluding service users as criminal subjects. This study recommends revising and strengthening regulations to close legal loopholes, improve law enforcement, and protect vulnerable groups against sexual exploitation, ultimately ensuring justice and legal certainty for all parties concerned.